2022
DOI: 10.1088/2515-7620/ac693a
|View full text |Cite
|
Sign up to set email alerts
|

CrAssphage as an indicator of groundwater-borne pollution in coastal ecosystems

Abstract: Novel approaches for monitoring coastal water quality changes and identifying associated contaminant source(s) are of growing importance as climate change and population redistribution to coastal zones continue to impact coastal systems. CrAssphage, a virus found in the human gut and shed with fecal matter, is currently gaining popularity as an indicator of human fecal contamination in surface water and groundwater. Here we demonstrate that DNA assays targeting crAssphage genetic fragments can be used to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Increased levels of crAssphage within reclaimed water heighten the probability of pathogenic viruses. Recent studies have also shown crAssphage to be a robust indicator of fecal contamination in the environment and in different water matrices [ 22 , 23 , 35 , 36 , 43 , 44 , 55 , 56 ]. However, the correlation between crAssphage and the presence of human viral pathogens is not clear and further research is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of crAssphage within reclaimed water heighten the probability of pathogenic viruses. Recent studies have also shown crAssphage to be a robust indicator of fecal contamination in the environment and in different water matrices [ 22 , 23 , 35 , 36 , 43 , 44 , 55 , 56 ]. However, the correlation between crAssphage and the presence of human viral pathogens is not clear and further research is needed.…”
Section: Resultsmentioning
confidence: 99%